2013
DOI: 10.1080/17477891.2013.837024
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of private-vehicle evacuation clearance times along the US Gulf Coast

Abstract: This study uses multilevel regression analysis to examine the effect of social characteristics and the built environment on clearance time under an evacuation scenario. The primary unit of analysis is the US Census tract (N = 1660), nested within 31 incorporated places spanning five US states. The dependent variable is an estimate of clearance time in hours derived using network analysis techniques within a geographic information system. We find that tracts with a more peripheral location, more female resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…On one hand, there are scholars who provide us with diverging findings. For instance, Berg and Wilson () found that along the U.S. Gulf Coast, people with higher income are having more problems with evacuation. However, the main reason for their problems is that they are living in more peripheral areas—so it is a very context‐specific situation.…”
Section: The Linkages Between Demographic and Natural Hazards Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, there are scholars who provide us with diverging findings. For instance, Berg and Wilson () found that along the U.S. Gulf Coast, people with higher income are having more problems with evacuation. However, the main reason for their problems is that they are living in more peripheral areas—so it is a very context‐specific situation.…”
Section: The Linkages Between Demographic and Natural Hazards Researchmentioning
confidence: 99%
“…Further publications focus on differences regarding risk‐related behavior. They argue that women are more likely to have risk averse behavior (Kellens et al, ) and tend to need more time to evacuate (in this case because women are more likely to reside in places that are difficult to evacuate; Berg & Wilson, ), or point to a positive association of female gender with following authority's recommendations in the case of an event (Kyne & Donner, ). However, following their meta‐analysis of hurricane evacuation studies, Huang et al () doubt that there is any significant correlation between female gender and evacuation behavior.…”
Section: The Linkages Between Demographic and Natural Hazards Researchmentioning
confidence: 99%
“…Tracts outside of Beltway 8 where the SoVI trend line increased are typically more affluent (e.g., Pasadena, Taylor Lake, Deer Park) underscoring that vulnerability is a multidimensional concept, extending beyond income and poverty (e.g., aged population in Taylor Lake). Further, the finding that tracts located roughly midway between the central city and fringe are where the SoVI trend line increased most frequently highlights the importance of better understanding of vulnerability within suburban areas given that congestion and lower connectivity in more affluent, fringe areas could increase evacuation times during an emergency (Berg and Wilson 2013).…”
Section: Temporal Changes Of Social Vulnerabilitymentioning
confidence: 99%